Let $f: W \rightarrow W$ be defined as $f(n)=n-1,$ if is odd and $f(n)=n+1,$ if $n$ is even. Show that $f$ is invertible. Find the inverse of $f$. Here, $W$ is the set of all whole numbers.
It is given that:
$f: W \rightarrow W$ is defined as $f(n)=\left\{\begin{array}{ll}n-1 & \text { If } n \text { is odd } \\ n+1 & \text { If } n \text { is even }\end{array}\right.$
For one-one
Let $f(n)=f(m)$
It can be observed that if $n$ is odd and $m$ is even, then we will have $n-1=m+1$
$\Rightarrow n-m=2$
However, this is impossible. Similarly, the possibility of $n$ being even and $m$ being odd can also be ignored under a similar argument.
$\therefore$ Both $n$ and $m$ must be either odd or even. Now, if both $n$ and $m$ are odd,
Then, we have $f(n)=f(m)$
$\Rightarrow n-1=m-1$
$\Rightarrow n=m$
Again, if both $n$ and $m$ are even,
Then, we have
$f ( n )= f ( m )$
$\Rightarrow n +1= m +1$
$\Rightarrow n=m$
$\therefore f$ is one-one.
For onto
It is clear that any odd number $2 r+1$ in co-domain $N$ is the image of $2 r$ in domain $N$ and any even number $2 r$ in co-domain $N$ is the image of $2 r +1$ in domain $N$.
$\therefore f$ is onto.
Hence, $f$ is an invertible function.
Let us define $g: W \rightarrow W$ as $(m)=\left\{\begin{array}{ll}m+1 & \text { If } m \text { is even } \\ m-1 & \text { If } m \text { is odd }\end{array}\right.$
Now, when $n$ is odd
$g o(n)=g(f(n))=g(n-1)=n-1+1=n$ and
When $n$ is even
$g o(n)=g(f(n))=g(n+1)=n+1-1=n$
Similarly,
When $m$ is odd
$f o(m)=f(g(m))=f(m-1)=m-1+1=m$ and
When $m$ is even $f o(m)=f(g(m))=f(m+1)=m+1-1=m$
$\therefore $ $g o f= I w$ and $f o g= Iw$
Thus, $f$ is invertible and the inverse of $f$ is given by $f^{1}=g$, which is the same as $f$ .
Hence, the inverse of $f$ is $f$ itself.
It is easy to see that $f$ is one-one and onto, so that $f$ is invertible with the inverse $f^{-1}$ of $f$ given by $f^{-1}=\{(1,3),(3,2),(2,1)\}=f$
Let f : $R \to R$ be defined by $f\left( x \right) = \ln \left( {x + \sqrt {{x^2} + 1} } \right)$ , then number of solutions of $\left| {{f^{ - 1}}\left( x \right)} \right| = {e^{ - \left| x \right|}}$ is
Which of the following function is inverse function
If the function $f : R \to R$ is defined by $f(x) = log_a(x + \sqrt {x^2 +1} ), (a > 0, a \neq 1)$, then $f^{-1}(x)$ is
If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........